Nudging Healthier Journeys through Information Design (breakout presentation). (December 2017) - Bell, Adrian
Abstract : Background: Wayfinding is a common action in active transportation strategies and trail plans. Wayfinding used to be synonymous with maps and signs but is now a more nuanced area of communication cutting across the disciplines of graphic, public realm and digital design. Urban wayfinding design took a leap forward with the UK Legible London project in 2008. Here cognitive science was used to produce intricately planned and iconic map pylons that have been copied across the world. The process for producing the mapping was so new, that a digital system, the Living Map was built. Aim: Legible London is cited as a cause of measured increases in walking, but London is a unique city and it was not known if the techniques used would work in North America. The designers took their knowledge to Vancouver, Edmonton and Cleveland under separate commissions to find out. Method: Each city undertook independent evaluations of prototype walking wayfinding projects using the same principles as Legible London. Generally, the evaluations included public intercept or on-line surveys as well as group reviews. Results: Independent evaluation showed that between 57% to 82% of people interviewed stated they were willingness to walk more as a result of the wayfinding. Legible London surveys after wider roll out have suggested a 5% increase in walking in those areas may be attributed to wayfinding. This indicates that intention is leading to action and given the relative costs of wayfinding compared to infrastructure, that there is a potentially high return on investment for this area of work. Conclusions: The presentation will demonstrate how carefully planned and executed urban wayfinding can increase willingness to walk in our gridiron cities as well as tangled European streets. It will outline key features of good wayfinding and how it works to change behaviour. It will conclude by suggesting how new technology and city objectives could increase the role of wayfinding in smart active cities.